2020
DOI: 10.3390/su12031282
|View full text |Cite
|
Sign up to set email alerts
|

Potential Distribution of the Critically Endangered Chinese Pangolin (Manis pentadactyla) in Different Land Covers of Nepal: Implications for Conservation

Abstract: Anthropogenic activities have driven many wildlife species towards extinction. Among these species, the geographic distributions of many are poorly documented, which can limit the effectiveness of conservation. The critically endangered Chinese pangolin (Manis pentadactyla) is experiencing population decline throughout its range due to land-use changes and illegal trade for food and traditional medicine. Using distribution records and maximum entropy modeling, we predicted the potential distribution of the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…Currently, all the species are under Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES 2019). Nepal supports the occurrence of two pangolins species, Chinese pangolin (Manis pentadactyla) and Indian pangolin (M. crassicaudata) (Gurung et al 1996, Baral & Shah 2008, Jnawali et al 2011, Suwal 2011, Bhandari & Chalise 2014, Thapa et al 2014, Sharma 2017, Katuwal et al 2017, DNPWC & DoF 2018, Sharma et al 2020a, b, c, d, Suwal et al 2020. Globally, the species is reported up to 3000 m of elevation (Challender et al 2019), however in Nepal the species is found up to 2406 m of elevation (Thapa et al 2014).…”
Section: Introductionmentioning
confidence: 79%
“…Currently, all the species are under Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES 2019). Nepal supports the occurrence of two pangolins species, Chinese pangolin (Manis pentadactyla) and Indian pangolin (M. crassicaudata) (Gurung et al 1996, Baral & Shah 2008, Jnawali et al 2011, Suwal 2011, Bhandari & Chalise 2014, Thapa et al 2014, Sharma 2017, Katuwal et al 2017, DNPWC & DoF 2018, Sharma et al 2020a, b, c, d, Suwal et al 2020. Globally, the species is reported up to 3000 m of elevation (Challender et al 2019), however in Nepal the species is found up to 2406 m of elevation (Thapa et al 2014).…”
Section: Introductionmentioning
confidence: 79%
“…We suggest this is a consequence of reduced human disturbance through management intervention for wildlife conservation in GCA (PA). Healthy forests support the occurrence of Chinese pangolin (Katuwal et al, 2017; Sharma et al, 2020), which more common in PAs than non‐PAs in Nepal, and likely supports higher occurrence of prey species. Chinese pangolin's occurrence was greater in PAs reduced disturbances, typically >1,000 m from the human settlements, livestock grazing, and road access (Katuwal et al, 2017; Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Many settlements practicing agriculture are sparsely distributed within forested areas. Both forest and agricultural lands support the occurrence of Chinese pangolin (Katuwal et al, 2017; Sharma et al, 2020) and though livestock may not directly disturb Chinese pangolins, livestock guard dogs, and people do pose threats. We suggest the observed response of greater Chinese pangolin occupancy nearer to human settlements is in part a consequence of the dispersion of human settlements within forested areas.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 94% of potential M. pentadactyla habitat covering 28,768 km 2 in the mid-hill region of Nepal occur outside protected areas (Sharma et al 2020). Poaching is one of the major threats for the species in Nepal and pangolin scales are confiscated in the country regularly (Katuwal et al 2015).…”
Section: Resultsmentioning
confidence: 99%